2-Benzisothiazolylimino-5-benzylidene-4-thiazolidinones as protective agents against cartilage destruction. Issue 7 (1st April 2015) - Crascì, Lucia; Vicini, Paola; Incerti, Matteo; Cardile, Venera; Avondo, Sergio; Panico, Annamaria
Graphical abstract: Abstract: We report the synthesis, the antioxidant and the inhibitory activity (IC50 ) on metalloproteinases (MMPs) 3 and 13 of 2-benzo[ d ]isothiazolylimino-5-benzylidene-4-thiazolidinones. Their potential as protective agents in osteoarthritis (OA) was evaluated by biological assays on chondrocytes cultures, stimulated by IL-1β. The chondroprotective capability, related both to antioxidant activity and to inhibition of MMPs, was studied in vitro, by determining nitric oxide production and glycosaminoglycans release. Moreover, selected derivatives1h and1g was studied for nuclear factor kappaB (NF-κB) inhibition by Western Blot analysis and for MMP-3 protein release using ELISA test. The structure–activity relationship of tested compounds demonstrates a favorable effect of the para substitution on the 5-benzilydene ring. Compound1g shows a potent and selective activity on MMP-3 versus MMP-13. Accordingly, 1g possesses high antioxidant effect, NO lowering and GAGs restoring capability and also reduces the production of MMPs and NF-κB expression. Thus1g can be considered as new potential chondroprotective agents.